Pendampingan Aplikasi Smart Government dalam Ekosistem Desa Digital Terintegrasi di Desa Ambulu, Cirebon - Situmeang, Ilona Vicenovie Oisina; Kencana, Woro Harkandi; Meisyanti, Meisyanti; Rahmawati, Khina Januar; Nugroho, Herlin Setio; Lubis, Adiella Yankie (Universitas Muhammadiyah Surakarta, 2023)
Sustainable village development is currently supported by the development of information technology which continues to increase in realizing an integrated digital village ecosystem. This community service activity is carried out with partners PT Jekom which is a Smart Government application development company as a digital community service platform. The problem faced by Ambulu Village is that the village community has not been optimal in using this application. These obstacles are due to the lack of knowledge of the Ambulu people and socialization regarding the existence and use of the Smart Government application. As well as not maximally utilizing the features contained in the application. Activities are carried out using survey methods, in-depth interviews and FGDs, then action & communication stages through outreach and assistance to the local government and Ambulu Village community, as well as evaluation of the results of activities. As a result of this activity, the Ambulu village community gained knowledge about the integrated digital village ecosystem and the benefits of using the Smart Government application. There is an increase in the use of the application and from the constraints on the use of this application it becomes a recommendation for the village government and PT. Jekom partners in developing applications and using applications that are effective and efficient in realizing an integrated digital village ecosystem.